Occurrence of delayed-onset post-traumatic stress disorder: a systematic review and meta-analysis of prospective studies - Utzon-Frank, Nicolai; Breinegaard, Nina; Bertelsen, Mette; Borritz, Marianne; Eller, Nanna Hurwitz; Nordentoft, Mads; Olesen, Kasper; Rod, Naja Hulvej; Rugulies, Reiner; Bonde, Jens Peter (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVE ': 'Post-traumatic stress disorder (PTSD) develops according to consensus criteria within the first 1–6 months after a horrifying traumatic event, but it is alleged that PTSD may develop later. The objective was to review the evidence addressing occurrence of PTSD with onset >6 months after a traumatic event (delayed-onset PTSD). ' ' METHODS ': 'Through a systematic search in PubMed, EMBASE, and PsycINFO, we identified 39 studies with prospective ascertainment of PTSD. A meta-analysis was performed in order to obtain a weighted estimate of the average proportion of delayed-onset PTSD cases, and meta-regression was used to examine effects of several characteristics ' ' RESULTS ': 'Delayed-onset PTSD was reported in all studies except one, and the average prevalence across all follow-up time was 5.6% [95% confidence interval (95% CI) 4.3–7.3%]. The proportion with delayed-onset PTSD relative to all cases of PTSD was on average 24.5% (95% CI 19.5–30.3%) with large variation across studies. In six studies with sub-threshold symptom data, delayed-onset PTSD seemed most likely an aggravation of early symptoms. The proportion with delayed-onset PTSD was almost twice as high among veterans and other professional groups compared to non-professional victims. ' ' CONCLUSION ': 'Descriptive follow-up data suggest that PTSD may manifest itself >6 months after a traumatic event, delayed-onset PTSD most often, if not always, is preceded by sub-threshold PTSD symptoms, and a higher proportion of PTSD cases are delayed among professional groups. Contextual factors and biased recall may inflate reporting of PTSD and a cautious interpretation of prevalence rates seems prudent.
Keywords: accident; catastrophe; deployment; disaster; mental disease; meta-analysis; post-traumatic stress disorder; PTSD; review; systematic review; trajectory